A Cognitive Failure Model of Construction Workers' Unsafe Behavior. (8th July 2022) - Deng, Shuwen; Peng, Rui; Pan, Yonggang
Abstract : The construction industry is one of the most dangerous industries globally, and construction workers are the leading cause of safety accidents. Unsafe behavior research focuses on behavioral safety of observable behaviors and the safety culture of organizational behaviors. However, these studies lack a systematic and comprehensive explanation of unsafe behavior. Therefore, this study constructs a cognitive failure model based on cognitive safety theory to explain the mechanisms of construction workers' unsafe behaviors. Five main causes of cognitive link failure were derived from the cognitive process of construction workers' unsafe behaviors: safety vigilance, hazard identification, safety knowledge, safety behavior attitude, and professional skills. Questionnaires were developed based on five cognitive failure factors and validated by structural equation modeling. The results show that the cognitive failure model fits well, and all five cognitive failure factors may lead to construction workers' unsafe behaviors. Among the five cognitive failure factors, safety vigilance is the main cognitive failure factor in obtaining information link; hazard identification is the major cognitive failure factor in understanding information link; and safety behavior attitude is the chief cognitive failure cause for selecting response link. These findings deepen the understanding of construction workers' unsafe behavior mechanisms.